Serum Immunoglobulin G and M Levels in Attention Deficit Hyperactivity Disorder Children - AL-Hasnawi, Sawsan M. Jabbar; AL-Hasnawi, Abeer Thaher Naji; Noori, Mays Amer (Journal for ReAttach Therapy and Developmental Diversities, 2022)
Background and Objective: Inflammation and immune response are focused on recently for their possible role in development and pathophysiology of different neuropsychiatric disorders as Attention Deficit Hyperactivity Disorder (ADHD). However, a limited data is present within this research area. Different inflammatory markers could be associated with disease development. The objective of the study is to clarify the role of IgG & IgM in ADHD patients through measuring serum levels of these markers. Methods: a case-control study that included 90 participants, 45 as patients’ group of ADHD with age range 6-12 (35 males and 10 females), in addition to 45 healthy control group. Serum levels of IgM and IgG were measured by using ELISA test. Results: a significant association between elevated serum level of IgG antibody and ADHD patients was reported. In addition, significant diagnostic utility for IgG. while no significant association with IgM levels were found. Conclusion: the study concludes higher serum level of IgG which could be used as diagnostic biomarker for differentiating ADHD children from healthy children.